Kinetics of Formation and Characterization of Green Silver Nanoparticles of Ficus variegata Leaf Extract - Synodalia C. Wattimena; Violin Ririmasse; Amos Killay; Philipus J. Patty (Jurnal Kimia Sains dan Aplikasi, 2022)
This study aimed to determine the formation rate of silver nanoparticles synthesized using leaf extract of Ficus variegata and characterize their physical, chemical, and antibacterial properties against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli. For the formation rate determination, an empirical exponential model was proposed and used to fit the absorbance vs. time data (kinetics data). The surface plasmon resonance wavelength was measured using UV-Vis spectroscopy for physical and chemical characterization. The shape and size of the silver nanoparticles were characterized by transmission electron microscopy (TEM), and organic materials on the surface of the particles were identified by characterizing the associated chemical bonding using FTIR spectroscopy. For antibacterial assays, disc diffusion and spectrophotometric methods were used. The formation rates of the silver nanoparticles were 0.036 per hour or 1.0 x 10-5 s-1 (slower rate) and 0.767 per hour or 2.1 x 10-4 s-1 (faster rate). UV-Vis absorption spectrum indicated the surface plasmon resonance peak at 415 nm. Silver nanoparticles formed mainly were spherical, with a mean diameter of 26.5±0.7 nm. The FTIR spectrum indicated the presence of organic materials on the surface of the silver nanoparticles, which indicated the involvement of the extract as a reducing agent in particles formation. Antibacterial assay showed that synthesized silver nanoparticles inhibited the growth of both S. aureus and E. coli. The results from the disc diffusion method imply that the particles inhibited the growth of E. coli more effectively than S. aureus.